+0  
 
0
40
1
avatar+836 

Let \(f(x) = ax^7 + bx^3 + cx - 5.\) If \(f(-7) = 7\) then find \(f(7).\)

 Dec 27, 2018
 #1
avatar+94453 
+1

f(-7)  =   

 

a(-7)^7 + b(-7)^3 + c(-7) - 5  = 7

 

a(-1)^7 * (7)^7   +  b (-1)^3 * (7)^3  + c (-1)(7) - 5  = 7

 

-a(7)^7  - b (7)^3  - c (7) - 5   =  7

 

- ( a(7)^7 + b (7)^3 + c(7)  )   = 12

 

a(7)^7 + b(7)^3 + c(7)  =  -12

 

So

 

a(7)^7 + b(7)^3 + c(7)  - 5   =  -12 - 5

 

f (7)   =   -17

 

 

cool cool cool

 Dec 27, 2018
edited by CPhill  Dec 27, 2018

21 Online Users

avatar
avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.